Islamic Finance and Environmental Sustainability: Empirical Insight from OIC Countries - Irfany, Mohammad Iqbal; Utami, Annisa Dwi; Lubis, Deni; Ramadhini, Fiona; Suwari, Lalacitra Fitri; Maula, Nisrina Rafelia; Fitriyatustany, Fitriyatustany; Haq, Daffa Aqomal (International Journal of Energy Economics and Policy, 2024)
Environmental degradation remains a significant global challenge, particularly in the Organization of Islamic Cooperation (OIC) countries. This study primarily examines the impact of Islamic finance, proxied by two indicators, namely Islamic financial assets and Islamic banking financing, and other variables including Gross Domestic Product (GDP), Foreign Direct Investment (FDI), urbanization, renewable energy adoption, and forest area, on CO2 emissions. This study revealed that Islamic financial assets had a negative impact on CO2 emissions, highlighting their importance in supporting green investments and sustainability. However, Islamic banking financing has little influence on emissions reduction, most likely due to carbon-intensive initiatives. Furthermore, GDP growth increases emissions, although FDI, urbanization, and forest areas help to lower them. These findings underscore Islamic finance's critical role in fostering sustainable development, as well as the necessity for better green Islamic financing policies in OIC member nations. The findings also provide important insights for policymakers working to balance economic growth with environmental sustainability in Islamic finance.